2021
DOI: 10.3390/jcdd8090100
|View full text |Cite
|
Sign up to set email alerts
|

New Interventional Therapies beyond Stenting to Treat ST-Segment Elevation Acute Myocardial Infarction

Abstract: Myocardial infarction remains the principal cause of death in Europe. In patients with ST-segment-elevation myocardial infarction (STEMI), a promptly revascularization with primary percutaneous intervention (PCI) has transformed prognosis in the last decades. However, despite increasing successful PCI procedures, mortality has remained unchanged in recent years. Also, due to an unsatisfactory reperfusion, some patients have significant myocardial damage and suffer left ventricular adverse remodeling with reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Thanks to the advancement of emergency care, most of the patients that present with an acute myocardial infarction with ST-elevation can now benefit from a prompt revascularization strategy [ 135 ]. Despite successful revascularization, up to 20% of patients surviving an ST-elevation myocardial infarction are hospitalized with HF in the first year after the event [ 136 ]. After revascularization, the underlying pathophysiological basis of myocardial damage switches from irreversible ischemia and cell necrosis to transient ischemia and ischemia-reperfusion injury.…”
Section: Ischemic Injury Modelsmentioning
confidence: 99%
“…Thanks to the advancement of emergency care, most of the patients that present with an acute myocardial infarction with ST-elevation can now benefit from a prompt revascularization strategy [ 135 ]. Despite successful revascularization, up to 20% of patients surviving an ST-elevation myocardial infarction are hospitalized with HF in the first year after the event [ 136 ]. After revascularization, the underlying pathophysiological basis of myocardial damage switches from irreversible ischemia and cell necrosis to transient ischemia and ischemia-reperfusion injury.…”
Section: Ischemic Injury Modelsmentioning
confidence: 99%
“…Multiple studies have described worsening necrosis after reperfusion, so-called "reperfusion injury". After major achievements in shortening the time to reperfusion and establishing complete reperfusion by pPCI, efforts are being made to minimize "ischemia-reperfusion" and "reperfusion" injury, using interventions started before, during and immediately after reperfusion [9,10]. Many agents and interventions have shown beneficial effects in decreasing reperfusion injury in animal models but have failed to show positive impact in patients with STEMI [11][12][13].…”
Section: The Potential Deleterious Effect Of Aspirin In Myocardial In...mentioning
confidence: 99%
“…Then, the balloon is deflated allowing systolic venous drainage (Figure 4 ). 73 The capacity of these techniques to provide cardioprotection relies on several aspects. First, canine models have shown that increasing coronary sinus pressure allows redistribution of blood flow to the endocardial layers.…”
Section: Coronary Sinus Interventionsmentioning
confidence: 99%
“…The catheter, which is connected to a console, is able to monitor coronary sinus pressure and automatically repeat inflations and deflations. Reproduced from Vidal‐Calés et al 73 under the terms and conditions of the Creative Commons Attribution (CC‐BY) license (https://creativecommons.org/licenses/by/4.0/).…”
Section: Coronary Sinus Interventionsmentioning
confidence: 99%